Learning Media for Bottom Passing Techniques During Volleyball Games - Dessy Wardiah; Ngalimudin Marzuki; Jujur Gunawan Manullang (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The research project aimed to create effective learning tools for mastering bottom-passing techniques in the context of volleyball gameplay. The study focused specifically on the students of MA Al-Akbar Air Kumbang, with the use of image-based media as the primary instructional tool. The goal was to design a comprehensive and engaging learning experience that would enhance the students' understanding and performance of bottom passing techniques in volleyball. Materials and Methods. The methodology employed in this study involves the use of research and development methods that are based on the ADDIE development model. This model is widely used in instructional design and involves five phases, which are analysis, design, development, implementation, and evaluation. By following this approach, the researchers aim to ensure that the final product of their research is effective, efficient, and meets the needs of the intended audience. Results. A comprehensive study has been conducted to develop a volleyball learning model for students of MA AL-Akbar Class XI. The learning model has been packaged in the form of a book, which includes image media. The model has undergone thorough validation by experts and has been deemed feasible and valid. The model is expected to enhance students' understanding of volleyball and improve their skills in the sport. Conclusion. According to the research findings, incorporating image media can greatly facilitate the learning process of the bottom passing technique in volleyball for students. The study suggests that visual aids have proven to be an effective tool in enhancing students' comprehension and mastery of the game technique.